Ruehssia quirinopolensis (Apocynaceae), a new species from the Cerrado Domain, Brazil - Isa Lucia de Morais; Fábio da Silva do Espírito Santo; Alessandro Rapini; Francisco Morales (Rodriguésia, 2021)
Abstract A new species of Apocynaceae, Ruehssia quirinopolensis, endemic to Serra da Confusão do Rio Preto and Serra da Igrejinha, Quirinópolis, state of Goiás, Brazil, is described and illustrated. It resembles R. rupestris, differing by the white corolla, adaxially villose and with a longer tube, and by its corona lobes with the upper portion lanceolate. Besides a distribution map for the new species, we provide a key to identify the nine species of Ruehssia that occur in Goiás. Ruehssia quirinopolensis is assessed here as Critically Endangered (CR).